The impact of Covid-19 pandemic on Medical School in a city in Northeast of Brazil (Research, Society and Development, 2023)
Introduction: With the social isolation resulting from the COVID-19 pandemic, student access to classrooms was extremely limited, especially during the beginning, when Universities were closed. From then on, the Ministry of Health, together with the Ministry of Education, approved the use of Distance Education for the Medicine Course. Objective: to analyze the benefits and limitations of Distance Education in Medicine during the pandemic, the acceptance, the possible failures in student learning and the effects on non-cognitive skills. Methodology: This is a cross-sectional, descriptive, quantitative study with undergraduate medical students from a teaching institution in the city of Teresina - PI. An online questionnaire was used to reach undergraduate students. Results and Discussion: Knowledge about the ambivalence between the benefits and limitations of Distance Education brings with it, in addition to the technological potential itself, the individual impact on the personal skills of those who are in training. Conclusion: Once Distance Education has been established in many educational institutions, this resource imposes studies and evaluations on its addition in the current scenario, since, in addition to technical knowledge, it requires, on the part of medical students, the development of non-cognitive skills, such as the active search for learning, leadership and overcoming procrastination.